Respon Pasar Atas Informasi Laba (Replikasi Ball dan Brown 1968) - Maharani, A. A. Istri Agung (E-Jurnal Akuntansi; Vol 8 No 1 (2014), 2014)
The capital market is where investors buy and sell shares. Information is needed by investors, one of which is earning information. This study is conducted to provide empirical evidence of market response due to unexpected earnings information. Research was focused at the Indonesian Stock Exchange. The number of samples used is 206 companies listed in Indonesia Stock Exchange period 2010-2012 by simple random sampling method. Data collected by non-participant observation method. T test is used as analysis technique. Based on the result, the market responded to unexpected earnings information, and the responses are in line with the announced earnings information. It can be concluded that the market, especially investors, would tend to make transactions based on earning information. When a company's earning is below expectations, transactions tend to decrease share price. When earning is above expectations, transactions tend to increase share price.
Keywords: earnings, market responds, abnormal return